Identification of Psychological Factors That Cause And How to Handle Suicide in South Korea Based on Psychological Autopsi - Hasna Nafila Febianti; Yusti Probowati; Mary Philia Elisabeth (Psikostudia : Jurnal Psikologi, 2024)
The suicide rate in South Korea is high among OECD countries with a total of 4657 suicides in Incheon city and only 1% participating in psychological autopsies. This article focuses on the psychological factors that cause suicide and the government's efforts to prevent suicide. The purpose of this study is to identify based on psychological factors regarding the causes and ways of handling suicides in South Korea seen based on the results of psychological autopsi. This research was conducted using a qualitative approach using the library research method. The results showed that the highest causes of suicide are mental health problems, physical health, financial problems. The most common methods of suicide are hanging and jumping from a height. The South Korean Government's efforts to reduce suicides The Ministry of Health and Welfare established the Korea Psychological Autopsy Center (Korea Foundation for Suicide Prevention) to establish evidence-based suicide prevention policies. The Korea Foundation for Suicide Prevention developed the Korean Psychological Autopsy Checklist (K-PAC), a semi-structured interview tool, by extracting common questions through a review of domestic and foreign literature and selecting items appropriate to the Korean situation. The implications of this study can be a reference for guidelines for other countries to address and prevent the high number of suicides in other countries, especially Indonesia. In addition, South Korea's preventive measures can be a morning focus for mental health survivors in IndonesiaTingkat bunuh diri di Korea Selatan tergolong tinggi diantara negara OECD yaitu total 4657 orang bunuh diri di kota Incheon dan hanya ada 1% yang berpartisipasi dalam autopsi psikologis. Artikel ini berfokus pada faktor psikologis penyebab terjadinya bunuh diri serta upaya pemerintah dalam mencegah bunuh diri. Tujuan penelitian ini adalah untuk mengidentifikasi berdasarkan faktor psikologis mengenai penyebab dan cara penanganan kasus bunuh diri di Korea Selatan yang dilihat berdasarkan hasil autopsi psikologis. Penelitian ini dilakukan menggunakan pendekatan kualitatif dengan menggunakan metode kajian kepustakaan (library research). Hasil penelitian menunjukkan penyebab paling tinggi bunuh diri yaitu masalah kesehatan mental, kesehatan fisik, masalaah keuangan. Metode bunuh diri yang paling sering dilakukan adalah gantung diri dan lompat dari ketinggian. Upaya Pemerintah Korea Selatan untuk mengurangi kasus bunuh diri Kementerian Kesehatan dan Kesejahteraan mendirikan Pusat Autopsi Psikologi Korea (Korea Foundation for Suicide Prevention) untuk menetapkan kebijakan pencegahan bunuh diri berbasis bukti. Yayasan Korea untuk Pencegahan Bunuh Diri mengembangkan Daftar Periksa Autopsi Psikologi Korea (K-PAC), alat wawancara semi-terstruktur, dengan mengekstrak pertanyaan umum melalui tinjauan literatur domestik dan asing dan memilih item yang sesuai dengan situasi Korea. Implikasi penelitian ini dapat menjadi referensi pedoman bagi negara lain untuk mengatasi dan mencegah tingginya kasus bunuh diri  khususnya Indonesia. Selain itu, tindakan preventif yang dilakukan Korea Selatan dapat menjadi fokus pagi para penyintas kesehatan mental di Indonesia.